Edentulism and all-cause mortality among Brazilian older adults: 11-years follow-up - Eduardo José Pereira OLIVEIRA; Luciana Correia ALVES; Jair Licio Ferreira SANTOS; Yeda Aparecida de Oliveira DUARTE; Fabíola BOF DE ANDRADE (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract We assessed the association between edentulism and all-cause mortality among community-dwelling older adults from São Paulo, Brazil, from 2006 to 2017. This prospective cohort study used data from the Health, Well-being and Aging Study (SABE, Portuguese acronym). Edentulism was evaluated by means of clinical oral examination and all-cause mortality data were obtained from state official records. Covariates included socioeconomic factors (age, sex, and schooling); health behavior (smoking, alcohol intake, and physical activity); dental care (prostheses use); general health (multimorbidity); and nutritional status (underweight). Kaplan-Meier survival curves were stratified by edentulism and compared using the log-rank test. Cox proportional hazards model was applied to calculate hazard ratios (HRs) for the association between edentulism and mortality after adjusting for covariates. The study sample included 1,687 participants (age, 60-102 years; edentulous: 47.2%). In the 11 years of follow-up, we analyzed 10,494 person-years and 566 deaths. In bivariate analysis, edentulous older adults were found to be at a higher risk of dying from all causes than the dentate participants (HR: 1.81; 95%CI: 1.53-2.15). After sequential adjustment for socioeconomic factors, health behavior, dental care, general health, and nutritional status, this association was attenuated, but remained significant (HR: 1.34; 95%CI: 1.10-1.63). In conclusion, edentulism is a significant predictor of all-cause mortality among older adults.